Effect of Crude Oil Polluted Water on the Organs of Cockerel Reared under Intensive System - Akporhuarho , P.O. (International Journal of Poultry Science, 2011)
Data from sixty day old Harco cockerel were used to determine the effect of Crude oil contaminated water on the internal organs of cockerel. There were four treatment groups with fifteen replicates each. Treatment one (T1) which received crude oil free water served as control. Treatment 2, 3 and 4 received crude oil contaminated water at the rate of 5 ml, 10 ml and 15 ml respectively. Both feed and water were provided ad libitum. The experiment lasted for eight weeks. At the end of the experiment two birds were picked randomly from each compartment and slaughtered for post mortem examination, from the result gizzard, heart, liver and spleen, were significantly (p<0.05) depressive as a result of the toxic effect of crude oil, while the intestine and testis were not significantly (p<0.05) affected. This could be as a result of the body’s ability to build up resistance against the toxic effect of crude oil.